1996
DOI: 10.1007/bf00014884
|View full text |Cite
|
Sign up to set email alerts
|

Leaflet photosynthesis rate and carbon metabolite accumulation patterns in nitrogen-limited, vegetative soybean plants

Abstract: Prolonged inorganic nitrogen (NO3 (-)+NH4 (+)) limitation of non-N2-fixing soybean plants affected leaflet photosynthesis rates, photosynthate accumulation rates and levels, and anaplerotic carbon metabolite levels. Leaflets of nitrogen-limited (N-Lim), 27-31-day-old plants displayed ≈ 15 to 23% lower photosynthesis rates than leaflets of nitrogen-sufficient (N-Suff) plants. In contrast, N-Lim plant leaflets displayed higher sucrose and starch levels and rates of accumulation, as well as higher levels of carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 42 publications
0
6
0
1
Order By: Relevance
“…Accumulation of sucrose and starch was observed in leaves of tobacco (Paul and Driscoll 1997; see also Rufty et al 1988) upon sudden withholding of N from the watering solution. And even after long-term acclimation to N limitation, leaves of spinach (Robinson 1997), cotton (Wong 1990), soybean (Robinson 1996), and wheat (Rogers et al 1996) were found to accumulate elevated levels of nonstructural carbohydrates, particularly at predawn. In the present study, leaves of Nlimited spinach also possessed higher levels of all measured carbohydrates at predawn on either a leaf area or dry-weight basis when compared to N-replete spinach (Table 2), indicating a source-sink imbalance.…”
Section: Resultsmentioning
confidence: 98%
“…Accumulation of sucrose and starch was observed in leaves of tobacco (Paul and Driscoll 1997; see also Rufty et al 1988) upon sudden withholding of N from the watering solution. And even after long-term acclimation to N limitation, leaves of spinach (Robinson 1997), cotton (Wong 1990), soybean (Robinson 1996), and wheat (Rogers et al 1996) were found to accumulate elevated levels of nonstructural carbohydrates, particularly at predawn. In the present study, leaves of Nlimited spinach also possessed higher levels of all measured carbohydrates at predawn on either a leaf area or dry-weight basis when compared to N-replete spinach (Table 2), indicating a source-sink imbalance.…”
Section: Resultsmentioning
confidence: 98%
“…Nota-se que plantas cultivadas sob altos níveis de nitrogênio tendem a reduzir o fluxo de carbono em direção à formação de amido e promover aumentos na síntese de ácidos orgânicos que podem ser utilizados como esqueletos de carbono para a formação de aminoácidos (SCHEIBLE et al, 1997). Ao contrário, quando a deficiência de nitrogênio é induzida, ocorre redução na demanda por fotoassimilados para a formação de aminoácidos e proteínas e, conseqüentemente, aumento na disponibilidade de hexoses que podem ser utilizadas para a produção de amido (ROBINSON, 1996). Adicionalmente, a redução na concentração de Pi citossólico (Figura 4B), que dificulta a saída da triose fosfato dos cloroplastos, também pode ter contribuído para a formação de amido das plantas cultivadas sob deficiência de nitrogênio.…”
Section: Resultsunclassified
“…metabolic pathways) and behavioural mechanisms may account for the increased heat production and respiratory C loss created by DIT (Zanotto et al 1997, Darchambeau et al 2003, Trier and Mattson 2003). Aquatic bacteria and autotrophs also can increase respiration when faced with high quantities of DOC or light (respectively) relative to nutrients (Robinson 1996, Alcoverro et al 2000, Smith and Prairie 2004). Significant quantities of excess C can also be exuded by algae growing under high light, low nutrient conditions (Berman‐Frank and Dubinsky 1999, Goto et al 1999).…”
Section: Release and Storage Of Resourcesmentioning
confidence: 99%
“…Animals can change their ingestion rate and degree of food selectivity to alter the balance of elements or biochemicals available for growth (Bairlein 1996, Witmer 1998, Plath and Boersma 2001, Raubenheimer and Simpson 2003. Omnivorous feeding habits or dietary mixing of heterogeneous food sources may also increase the acquisition of the limiting nutrient, as has been observed for vertebrates (Izhaki andSafrel 1989, Rode andRobbins 2000), crustaceans (DeMott 1998, Acharya et al 2004, and insects (Denno andFagan 2003, Raubenheimer andSimpson 2003). Organisms using such physiological mechanisms (e.g.…”
Section: Acquisition Of Resourcesmentioning
confidence: 99%